Correction to: Evaluating changes in electronic gambling machine policy on user losses in an Australian jurisdiction - Matthew Stevens; Charles Livingstone (BMC, 2019)
It was highlighted that in the original article [1] Fig. 3 and Fig. 4 legends were incorrect. This Correction article shows Fig. 3 and Fig. 4 with their correct legend.